Integrated Assessment of the Impact of Cropland Use Transition on Food Production Towards the Sustainable Development of Social–Ecological Systems - Yixin Liao; Xiaojun Lu; Jialin Liu; Jiajun Huang; Yue Qu; Zhi Qiao; Yuangui Xie; Xiaofeng Liao; Luo Liu (Agronomy)
Understanding the impact of changes in cropland on food production is crucial for economic development and social stability. In recent years, rapid economic growth and frequent population migration in Guangdong Province have significantly changed cropland use and patterns, posing challenges to cropland protection and food security. This study utilized Landsat-4/5/7/8 time-series imagery from the Google Earth Engine and combined it with deep learning techniques to identify long-term cropland use from 1991 to 2020. Then the Global Agro-Ecological Zones model was applied to assess the impact of various cropland use changes on grain production potential (GPP). On this basis, the intrinsic relationship between population, economic development, and food production was further explored using the center of gravity model and spatial mismatch model. The study finds that Guangdong Province’s cropland area has decreased by approximately 34.16%. The annual average loss due to non-agricultural use and abandonment is 2.75 thousand km2 and 3.09 thousand km2, respectively, while the average yearly compensated cropland area is 2.94 thousand km2. The actual annual food loss could meet the needs of about 4.6 million people. Furthermore, non-agriculturalization is the main way of losing GPP, and the reduction of GPP caused by abandonment cannot be underestimated. When considering the GPP loss due to abandonment, new GPP has not fully compensated for lost GPP. Guangdong Province has rapidly decreased the coordination between food production, population, and economic development, leading to considerable contradictions in the social–ecological systems. Finally, the movement of cropland and population centers in opposite directions has intensified the decoupling phenomenon. The results can guide the development of refined cropland protection policies and promote sustainable development of social–ecological systems.